2018
DOI: 10.3390/diagnostics8030045
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body MRI with Diffusion-Weighted Imaging in Bone Metastases: A Narrative Review

Abstract: Whole body magnetic resonance imaging (MRI) with diffusion-weighted imaging (WB-MRI-DWI) is currently emerging as a diagnostic technique in the evaluation of bone metastases from breast, prostate, lung, thyroid, and melanoma tumors. The most relevant articles regarding the detection of solid tumor bone metastases with MRI have been reviewed and cited. The imaging methods currently used in the detection of bone metastases are bone scintigraphy, computed tomography (CT), and positron emission tomography (PET/CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
(39 reference statements)
2
31
0
1
Order By: Relevance
“…Furthermore, in case of vertebral metastases, MRI is essential for the assessment of epidural, nerve, and spinal cord involvement, playing a pivotal role in the pre-surgical workup [ 21 , 22 ]. Whole-body (WB) MRI with diffusion-weighted imaging (MRI-DWI) is a promising imaging technique in the evaluation of BM from different solid tumours, including DTC [ 23 ]. The added value of DWI is the addiction of functional information to morphological sequences: being able to detect differences in cellularity of malignant bone marrow disorders with respect to the normal bone marrow, it might help in differentiating between malignant and benign lesions.…”
Section: The Role Of Anatomic and Functional Imagingmentioning
confidence: 99%
“…Furthermore, in case of vertebral metastases, MRI is essential for the assessment of epidural, nerve, and spinal cord involvement, playing a pivotal role in the pre-surgical workup [ 21 , 22 ]. Whole-body (WB) MRI with diffusion-weighted imaging (MRI-DWI) is a promising imaging technique in the evaluation of BM from different solid tumours, including DTC [ 23 ]. The added value of DWI is the addiction of functional information to morphological sequences: being able to detect differences in cellularity of malignant bone marrow disorders with respect to the normal bone marrow, it might help in differentiating between malignant and benign lesions.…”
Section: The Role Of Anatomic and Functional Imagingmentioning
confidence: 99%
“…Bone lesions deriving from NENs appeared predominantly osteoblastic (up to 83% of cases), whereas osteolytic or mixed patterns were less frequent [11,41]. MRI was shown to have a sensitivity of nearly 100% for the detection of bone marrow metastases [13,68], and particularly, whole-body MRI associated with body diffusion-weighted imaging (DWI) better distinguished benign from malignant bone lesions [69]. Recently, no significant differences between CT and MRI for the detection of BMs have been demonstrated [18].…”
Section: Diagnosis Of Bmsmentioning
confidence: 99%
“…Detection of metastases by CT requires destruction of cortical or trabecular bone, adjacent sclerotic changes, or identification of soft tissue attenuation within the normal fat-attenuation marrow. In contrast, skeletal metastases on MR can be characterized by signal abnormality of the bone marrow on T1, STIR, and diffusion-weighted sequences [36][37][38][39][40]. Numerous studies have shown that MR is more sensitive than CT alone in the detection of focal marrow replacing lesions and that the higher soft tissue contrast provided by MR allows for better delineation of extra-osseous tumor spread and spinal cord compression (Fig.…”
Section: Mr Component Of Pet/mr and Protocol Considerationsmentioning
confidence: 99%